Biochemical and histochemical chenges in the activity of succinate dehydrogenase and ATP-ase in mitochondria of kidneys rats by acute intoxication - Dikal, M. V.; Ferenchuk, Ye. O.; Bilous, T. M.; Grytsiuk, M. I.; Kopchuk, T. G. (Journal of Education, Health and Sport, 2018)
Оbject of the study was to evaluate activities of succinate dehydrogenase and ATP-ase in mitochondria of kidney under conditions of toxic influence of 2,4-dinitrophenol. The experiment was conducted on 60 male albino rats. Toxic damage was caused by 0.1% solution of 2,4-dinitrophenol intraperitoneally in the dose of 3 mg / kg. The histochemical, biochemical and statistical methods of research were used. Mitochondria isolation was performed using the method of differential centrifugation. Determination of mitochondrial succinate dehydrogenase activity consists in the restoration of potassium ferricyanide (K3[Fe (CN)6]), whose solution has a yellow color, to the colorless ferricyanide of potassium (K4[F (CN)6]) succinate by the action of succinate dehydrogenase. The activity of ATP-ase was determined by the accumulation of inorganic phosphate. The level of activity of succinate dehidrogenase was 39% lower than that of the control values. Whereas the level of activity of ATP-ase decreased by 48% in accordance with the control. Similar histochemical changes of the enzyme of the II complex of the mitochondrial respiratory chain were revealed. The findings revealed that 2,4-dinitrophenol produced significant biochemical and histochemical changes in the kidney of the rats. This led to a decrease enzyme activities and as a result to a discrepancy between the energy needs of the cell and energy production in the system of mitochondrial oxidative phosphorylation.